The forces exerted by the TE33A locomotive on the switch elements - ABDULLAYEV, Seidulla; BAKYT, Gabit; IZBAIROVA, Aliya; ABDULLAYEVA, Asel; TURSYNBAYEVA, Arailym (International Journal of Innovative Research and Scientific Studies, 2025)
The article discusses the forces that arise when a TE-33A diesel locomotive moves through a switch. The analysis of dynamic loads acting on rail threads, crosspieces, and other switch elements is carried out. The purpose of this article is to determine the efforts of the TE-33A diesel locomotive acting on the main elements of the railway track switch. The measurements were carried out in accordance with the requirements using a strain gauge measuring and computing complex consisting of certified and verified measuring instruments from the world’s leading manufacturers. As a result of theoretical analysis and experimental studies, the lateral and vertical forces transmitted by the wheels to the inner and outer rails of the transfer curve were determined when the TE-33A locomotive was moving along the R65 mark 1/11 switch. Possible causes of increased wear of the switch elements under the influence of the TE-33A diesel locomotive have been identified. Recommendations are proposed to reduce the negative impact on the switches, including optimizing driving modes. Based on the results obtained, diagrams of vertical and transverse forces were constructed, and indicators of the stress rate at maximum speed along the arrow of the locomotive in question were established.